Pengaruh Latihan Pendek Shadow Backhand terhadap Kemampuan Servis Pendek Backhand Siswa SMP Tamalatea Kabupaten Jeneponto - Nukrawi Nawir; Fahrizal Fahrizal; M. Rachmat Kasmad; Muh. Adnan Hudain; Sandi Situju (Departement of Mathematics Education, 2024)
This research is a quasi-experimental research which aims to determine the effect of basic shadow short serve technique training on the backhand short serve ability of Tamalatea Jeneponto Middle School students. This research method uses experiments with a quantitative approach. The research sample consisted of 30 students who were divided into 2 groups using radom sampling with a matching ordinal pairing design resulting in 15 students joining the experimental group and 15 students joining the control group who were not given training. The research results showed that there was a difference in the average results of students' pretest and posttest. The pretest results for the shadow training group were 20.73 to 27.67 after the posttest. Meanwhile, the control group who were not treated with pretest results obtained 20.60 to 21.87. The conclusion of the research is that there is a significant effect of shadow short serve training on the backhand short serve ability of Tamalatea Jeneponto Middle School students.